Evaluation of biosorption potential of Gracilaria corticata for the removal of hexavalent chromium from aqueous solutions using response surface methodology - K, Kumaraguru; Sureshkumar, P. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
In this study, the biosorption of chromium (VI) on Gracilaria corticata biomass marine algae, was investigated in a batch and continious system. The influence of process parameters including sorbent size (0.176 - 1.503 mm), sorbent dosage (3 -7 g/l), temperature (25 - 45°C), contact time (2 - 10 hrs) and agitation speed (50 - 250 rpm) on the sorption of chromium (VI) were performed using a full factorial central composite design (CCD). This result of the studies indicates that the optimum biosorption conditions of sorbent size, sorbent dosage, temperature, contact time and agitation speed were 0.5284 mm, 5.12 g, 35°C , 2 hours 58 minutes and 140 rpm, respectively. A higher value coefficient of determination R2 0.9799 evidenced the fitness of response surface methodology. The Langmuir and Freundlich isotherm models were applied to the equilibrium data. The Langmuir adsorption model was better than the other model. The maximum adsorption capacity of Gracilaria corticata was found to be 62.5 mg/g. The thermodynamic parameters like enthalpy (ΔH◦) and entropy (ΔS◦) were 34.57 (kJ/mol) and 0.1308 (kJ/mol K) respectively. The results showed that the biosorption of chromium (VI) by Gracilaria corticata is more endothermic and spontaneous.